Rethinking alternative livelihood projects for women of the pits: The case of Atiwa - Boateng, A. (DE GRUYTER Online, 2017)
Artisanal Small Scale Mining with its environmental, social, economic, and health impacts, is replacing agriculture as the main economic activity in sub-Saharan Africa. Mining activities have therefore become an economic activity in the rural mining areas, as a quick way to escape poverty. This exploratory qualitative study examines the factors behind the prevalence of women in the pit business, washing muddy sand for particles of gold, in the Atiwa district of Ghana. However, not much is known about the impact of the pit work on the women’s wellbeing. The goal is to understand the lived experiences of the women and explore ways they could be assisted. Findings from the study indicate that poverty, lack of economic opportunities, and unattractive rural poverty alleviation strategies have contributed to the plight of these women. The women could benefit from asset-based interventions that could redirect their work to projects that would enhance their livelihoods.
Journal Articles
Keywords: Artisanal mining; kolikoli (pit work); women; alternative livelihood; Atiwa; Ghana